A new war in Mozambique? - Bussotti, Luca (2014)
The political situation in Mozambique is agitated. At sunrise on April 4, a group of about 200 members of Renamo (National Resistance of Moçambique, the main opposition party) organized a meeting in Muxunguè (Chibabava, Province of Sofala). The FIR (Police of Rapid Intervention) then entered the meeting room in order to disperse the people. It seems that a woman died. As a reaction, in the night of the same day, a Renamo group attacked the Police Headquarters. Five people died and 11 were injured.